Protein splicing and its evolution in eukaryotes - Starokadomskyy, P.L. (Вiopolymers and Cell, 2010)
Inteins, or protein introns, are parts of protein sequences that are post-translationally excised, their flanking regions (exteins) being spliced together. This process was called protein splicing. Originally inteins were found in prokaryotic or unicellular eukaryotic organisms. But the general principles of post-translation protein rearrangement are evolving yielding different post-translation modification of proteins in multicellular organisms. For clarity, these non-intein mediated events call either protein rearrangements or protein editing. The most intriguing example of protein editing is proteasome-mediated splicing of antigens in vertebrates that may play important role in antigen presentation. Other examples of protein rearrangements are maturation of Hg-proteins (critical receptors in embryogenesis) as well as maturation of several metabolic enzymes. Despite a lack of experimental data we try to analyze some intriguing examples of protein splicing evolution. Інтеїни, або білкові інтрони, – це білкові послідовності, якi автокаталітично вирізаються після трансляції, зшиваючи фланкуючі ділянки (екстеїни). Такий процес названо білковим сплайсингом. Спочатку інтеїни виявлено у прокаріотів і одноклітинних еукаріотів. Але загальний принцип посттрансляційної перестановки білків еволюціонував разом із живою матерією. На сьогодні ціла низка білків у багатоклітинних організмів модифікується за механізмами, принципово схожими з білковим сплайсингом у бактерій. Ці процеси отримали назву білкового редагування. Найцікавішим випадком білкового редагування є «тасування» епітопів антигенів протеасомою, що відіграє важливу роль у процесі презентації антигену клітинами. Іншими прикладами слугують дозрівання Hg-білків (рецепторів, критичних для коректного протікання ембріогенезу) або дозрівання низки метаболічних ферментів. Незважаючи на брак експериментальних даних, в огляді зроблено спробу описати найяскравіші приклади еволюції у вищих еукаріотів. Интеины, или белковые интроны, являются частью белковой последовательности, которая самовырезается после трансляции, сшивая фланкирующие участки (экстеины). Такой процесс назван белковым сплайсингом. Изначально интеины обнаружены у прокариотов и одноклеточных эукариотов. Но общий принцип посттрансляционной белковой перестановки эволюционировал вместе с живой материей. На сегодня целый ряд белков у многоклеточных организмов подвергается модификациям, принципиально схожим с белковым сплайсингом у бактерий. Эти процессы получили название белкового редактирования. Наиболее интересным случаем белкового редактирования является «перетасовка» эпитопов антигенов протеасомами, что, по-видимому, может играть определенную роль в процессе презентации антигена клетками. Другими примерами служат дозревание Hg-белков (рецепторов, критических для корректного протекания эмбриогенеза) или дозревание ряда метаболических ферментов. Несмотря на недостаток экспериментальных данных, в обзоре сделана попытка описать наиболее яркие примеры эволюции белкового сплайсинга у высших эукариотов.